The Audienceâ€™s Acceptance of a Single Parent in The Film "Susah Sinyalâ€ - Muhammad Irawan Saputra; Alfiazahra Alfiazahra; Valenia Juvita Gunadi; Agustina Sitti Anggawen; Sinta Ayudiya Ariani (Communicatus: Jurnal Ilmu komunikasi, 2023)
Children raised by single parents often face more difficulties in family relationships than children raised in intact families. Single parents frequently struggle to balance work and parental responsibilities. Ernest Prakasaâ€™s film Susah Sinyal attempts to raise awareness of the phenomenon of single parenthood by depicting the relationship and struggles of a single mother and her daughter. The objectives of this study were to (1) examine how the audience interprets the representation of single parents in films, and (2) investigate how this representation influences the audienceâ€™s understanding of single-parent life in the real world. This study included five children raised by single parents. This is a descriptive study that is divided into two stages using the reception analysis method. The first step is to perform content analysis or encoding. The second stage is decoding, which includes a Focused Group Discussion (FGD). The findings indicate that the representation of single parents in the film has various meanings for the audience. They felt that the film accurately represented their point of view while others said no. This film does not provide many new ideas or alternative perspectives on single-parent family life. Furthermore, the message conveyed in this film could be a reflection of Indonesian society.